WORKSHOP DAN PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU PAUD PENAMBANGAN: WORKSHOP DAN PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA BAGI GURU PAUD PENAMBANGAN - Tirtoni, Feri; Luluk Iffatur Rocmah; Rofiqul Halim (Kanigara, 2024)
This community service aims to explore strategies for increasing the role of preschool teachers in implementing the independent curriculum. The method used in community service is the socialization method, through this service through the implementation of activities such as seminars and question and answer sessions. The conclusion of this community service reveals that the role of the teacher is the main driver, the essence of the concept of "Freedom to Learn" actually lies in the individual who learns. The main focus is to ensure that learning does not cause pressure or stress, but rather allows creativity, innovation, and freedom without limitations under the "Freedom to Learn" approach. "more appropriate to the stage of development of children who are basically still in the world of play, a natural learning process, with the aim of achieving intellectual freedom. The flow of learning objectives is defined as a series of learning objectives that are arranged logically according to the learning sequence from beginning to end. Each of these sub-elements needs to be facilitated in learning activities in the PAUD unit so that children receive holistic learning achievement elements.